Dual Sensory Loss, Mental Health, and Wellbeing of Older Adults Living in China - Heine, Chyrisse; Gong, Cathy Honge; Browning, Colette (Frontiers in Public Health, 2019)
Introduction: Deterioration in vision and hearing commonly occurs as adults age. Existing literature shows that Dual Sensory Loss (DSL) is a prevalent condition amongst older adults. In China, it has been estimated that 57.2% of the population experience DSL. Based on a small number of research papers, it has been identified that DSL influences mental health and wellbeing. The aims of this study were to explore the relationship between DSL and mental health and wellbeing in a sample of older adults residing in China; and investigate whether the comorbidities of functional dependency [Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL)] and chronic diseases influence the impacts of DSL on mental health and wellbeing. Method: The China Health and Retirement Longitudinal Study Wave 2, 2013 data collection of a sample of people aged 60 years and over (n = 8,268) was used in this study. The sensory loss variables selected for analysis included a combined variable of self-reported vision and hearing loss (DSL). Mental health was measured by depression, and general wellbeing was measured by life satisfaction. In addition, chronic diseases, and limitations in IADL and ADL were used to test how their comorbidities with DSL influence mental health and wellbeing. Results were analyzed descriptively and using regression and modeling techniques. Results and Discussion: DSL was significantly and positively associated with advanced age, having difficulty in any ADL or IADL and experiencing depression and less life satisfaction. The observed negative associations between DSL and mental health or wellbeing, are indirect and could be partially explained by its comorbidity with chronic diseases and relationship to functional limitations. It is recommended that health services in China screen for DSL in older people and develop integrated services to assist with appropriate management and rehabilitation of older people with DSL focusing on both functional and mental health issues.